The Role of Administrative Management Information Systems in Enhancing Operational Efficiency at PT. ABC - Siregar, Lenny Rotua Masriany; Hutapea, Maulin Elisabet Laurance; Malau, Roslin; Susrini, Susrini; Harahap, Amin (LPPPIPublishing, 2025)
In the digital transformation era, organizations are increasingly adopting Administrative Management Information Systems (AMIS) to enhance operational efficiency and competitiveness. This study explores the implementation of AMIS at PT. ABC using a mixed-methods approach, combining quantitative performance metrics with qualitative insights from managerial staff. The results indicate that AMIS significantly improves administrative task processing speed, reduces error rates, and lowers operational costs. Furthermore, the system fosters transparency, real-time decision-making, and cross-departmental collaboration. The integration of Artificial Intelligence and data governance protocols further elevates AMIS from a transactional tool to a strategic asset. However, challenges such as user resistance and digital literacy gaps highlight the importance of comprehensive training and change management. Overall, AMIS proves to be a critical enabler of operational excellence and digital transformation within PT. ABC.